Τρισάγιον – in the Byzantineand Old Bulgarian Liturgical Practice. Characteristics, Features and Use in the Liturgical Tradition of the Church - Ivanov, Ivan (Forum Theologicum Sardicense, 2025)
Ivan Ivanov, Τρισαγιον – in the Byzantine and Old Bulgarian Liturgical Practice. Characteristics, Features and Use in the Liturgical Tradition of the Church. The study focuses on the ecclesiastical, social, and political prerequisites for the formation of liturgical features in the Byzantine Empire and their impact on Old Bulgarian and Slavic liturgical traditions. It examines the characteristics of Byzantine and Old Bulgarian studies regarding liturgical and Eucharistic practices within the context of both Bulgarian and international liturgical research on the Liturgy and the Eucharist. Special attention is given to certain peculiarities of Byzantine liturgies, such as the Liturgy of St. John Chrysostom and the Liturgy of St. Basil the Great, as well as the Old Bulgarian Liturgy, with a particular focus on the role of the Trisagion. The study clarifies the connection between the Trisagion and the Liturgy of the Catechumens and the Liturgy of the Faithful. It proposes a liturgical and theological interpretation of the Trisagion in relation to Byzantine, Old Bulgarian, and Slavic traditions. Biblical and patristic foundations for the Trisagion of the Angels are explored, and comparisons are made with other forms of the Angelic song, such as the Cherubic Hymn and the Sanctus – Post-Sanctus. The study includes their presence in the liturgical life of the Church and their role as a theological phenomenon within Church life. The research is based on authentic ancient Byzantine, Old Bulgarian, and Slavic liturgical codices and prayer books (Euchologion), as well as on liturgical and Eucharistic texts (anaphors) found in Greek and Slavic liturgical books (Slujebnik). It demonstrates the connection between Byzantine prototypes and Byzantine theology, and the Old Bulgarian and Slavic models from the IX to the XV centuries, in which the Trisagion is a central component. Additionally, the study includes liturgical interpretations and analyses of medieval texts in comparison with modern liturgical practices of the Church.